The Nexus Between Public Enterprise Governance, Financial Performance, and Macroeconomic Vulnerabilities : An Application to Moldova - Hegazy, Amgad (IMF Working Papers; Working Paper ;, 2022)
Strong governance frameworks for public enterprises have long been an anchor of stability and efficiency underpinning their financial operations and performance. Cross-country experiences with the adoption of robust legal, regulatory and institutional arrangements-in line with international best practices- proved critical in reducing well-known risks and vulnerabilities from such companies, clarifying the role of the state, improving the management of state assets, and ensuring a level playing field for the private sector to prosper. Moldova's large public enterprise sector of over 900 companies faces elevated risks that amplify fiscal and macroeconomic vulnerabilities and undermine market competition, productivity, and private investment. Moldova stands to greatly benefit from strengthening its public corporate governance regime to put its public enterprises on a stronger footing, address vulnerabilities, and improve market structure.